2022
DOI: 10.2144/btn-2022-0064
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Violet Staining is a Reliable Alternative to Bicinchoninic Acid Assay-Based Normalization

Abstract: Experimental data with cells often require normalization. The frequently used bicinchoninic acid (BCA) assay, in fact, indicates protein content but is influenced by incubation time, pH etc. A simple, rapid and reliable alternative is desirable. Crystal violet stains nucleic acids and proteins and was used to reflect the cell number in 96-well plates. Calibration curves and comparison with BCA confirmed excellent goodness of fit (R2: 0.98), conformity (nonsignificant difference of BCA to crystal violet) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…To test this hypothesis, we designed ADCs that are susceptible or refractory to MUC16/CA125 HIO factor binding. Assays comparing their cytotoxicity against isogenic cell lines that were MUC16/CA125 positive or negative were quantified using methods confirmed to accurately measure cell growth kinetics and viability [ 23 ]. Our studies found that HIO factors can negatively impact alternative antibody-based formats such as ADCs similar to their parent IgG (Figs 2A and 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we designed ADCs that are susceptible or refractory to MUC16/CA125 HIO factor binding. Assays comparing their cytotoxicity against isogenic cell lines that were MUC16/CA125 positive or negative were quantified using methods confirmed to accurately measure cell growth kinetics and viability [ 23 ]. Our studies found that HIO factors can negatively impact alternative antibody-based formats such as ADCs similar to their parent IgG (Figs 2A and 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Antiproliferative effects of the rifamycins were investigated for all studied incubation periods using proliferation inhibition assays with crystal violet staining as described earlier (Nilles et al 2022a , b ; Peters et al 2006 ). Experiments were performed in three independent biological replicates with n = 8 wells for each concentration.…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved by multiplying the measured mean cellular volume of a LS180 cell (CASY cell counter, Schärfe System, Reutlingen, Germany) by the mean cell number of four wells of an identically prepared and treated cell culture plate. Experiments were conducted in duplicate (one plate for uptake experiments and a second plate for normalization via crystal violet staining (Nilles et al 2022a , b )) with four biological replicates for each concentration.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, cell proliferation showed sufficient cell proliferation effects at concentrations of 1% to 2% FBS for both CJ and MDCK cells. Interestingly, cell number comparison by CV staining [36] showed that CJ cells stained significantly stronger than MDCK cells (Fig. 4b).…”
Section: Resultsmentioning
confidence: 99%